Long-term clinical outcomes of carvedilol versus nebivolol in patients with ST-segment elevation myocardial infarction treated with second-generation drug-eluting stents: insights from a Korean nationwide multicenter prospective registry - Jihun Ahn; Hye Yon Yu; Seung-Woon Rha; Se Yeon Choi; Jae Kyeong Byun; Soohyung Park; Cheol Ung Choi; Youngkeun Ahn; Dongkyu Jin; Byoung Geol Choi (Frontiers in Cardiovascular Medicine, 2026)
Background Owing to the limited head-to-head comparative evidence between vasodilating β -blockers, this study aimed to assess long-term clinical outcomes of nebivolol vs. carvedilol in patients with ST-segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI) with second-generation drug-eluting stents (DES). Methods Data were obtained from the Korea Acute Myocardial Infarction Registry (KAMIR), including the KAMIR–National Institutes of Health (NIH) and KAMIR-V cohorts (2011–2020). Patients with STEMI who underwent successful PCI with second-generation DES and received either carvedilol or nebivolol were retrospectively analyzed. The primary endpoint was 3-year major adverse cardiac events (MACE). Secondary endpoints included individual MACE components, stent thrombosis, and heart failure–related rehospitalization. Inverse probability of treatment weighting (IPTW) was used to adjust for baseline differences. Results A total of 6,752 eligible patients with STEMI were identified, baseline differences were effectively minimized using IPTW analysis. Over a median follow-up of 3 years, nebivolol was associated with a higher MACE risk compared with carvedilol (11.1% vs. 9.6%; hazard ratio [HR] 1.176, 95% confidence interval [CI] 1.052–1.314, p = 0.005). All-cause mortality (4.4% vs. 3.4%; HR: 1.315, 95% CI: 1.102–1.569, p = 0.002) and revascularization (7.0% vs. 6.2%, p = 0.043; HR: 1.15, 95% CI: 1.00–1.32, p = 0.043) were also higher in the nebivolol group compared with carvedilol. Conclusions In this contemporary cohort of patients with STEMI treated with DES, carvedilol was associated with better long-term clinical outcomes, including lower risks of MACE and all-cause mortality, compared with nebivolol.